Exploring the Production of Urban Space : Differential Space in Three Post-Industrial Cities - Leary-Owhin, Michael Edema (Book collections on Project MUSE., 2016)
Manchester is now an iconic postindustrial city but what crucial role did Lord Michael Heseltine play in its spatial production? And how is space produced? What are the unexpected links between Manchester, Vancouver and Lowell Massachusetts? This book shows through meticulous original research how urban space is socially produced. The author uses archival and interview evidence to unravel the unexpected histories of the production of new diverse public spaces.